Are women who quit smoking at high risk of excess weight gain throughout pregnancy?. Issue 1 (December 2016) - Hulman, Adam; Lutsiv, Olha; Park, Christina; Krebs, Lynette; Beyene, Joseph; McDonald, Sarah
Abstract Background Smoking cessation has been reported to be associated with high total gestational weight gain (GWG), which itself is a risk factor for adverse maternal-infant outcomes. Recent studies have criticized conventional single measures of GWG, since they may lead to biased results. Therefore, we aimed to compare patterns of GWG based on serial antenatal weight measurements between women who: never smoked, quit during pregnancy, continued to smoke. Methods Participants (N  = 509) of our longitudinal study were recruited from seven antenatal clinics in Southwestern Ontario. Serial GWG measurements were abstracted from medical charts, while information on smoking status was obtained from a self-administered questionnaire at a median gestational age of 32 (27–37) weeks. GWG patterns were assessed by fitting piecewise mixed-effects models. First trimester weight gains and weekly rates for the last two trimesters were compared by smoking status. Results During the first trimester, women who never smoked and those who quit during pregnancy gained on average 1.7 kg (95 % CI: 1.4–2.1) and 1.2 kg (0.3–2.1), respectively, whereas women who continued smoking gained more than twice as much (3.5 kg, 2.4–4.6). Weekly rate of gain in the second and third trimesters was highest in women who quit smoking (0.60 kg/week, 0.54–0.65), approximately 20 and 50 % higher than in women who never smoked and those who smoked during pregnancy, respectively. Conclusions In this longitudinal study to examine GWG by smoking status based on serial GWG measurements, we found that women who quit smoking experienced a rapid rate of gain during the last two trimesters, suggesting that this high-risk group may benefit from targeted interventions.